2015
DOI: 10.1007/s40519-015-0179-y
|View full text |Cite
|
Sign up to set email alerts
|

Family lifestyle and childhood obesity in an urban city of Northern Italy

Abstract: Our findings support the relevance of environmental factors in childhood food consumption and BMI distribution among children in an urban city. This is the reason why we stress the need to design ad hoc interventions, which should be developed in accordance with the socio-economic peculiarities of a cosmopolitan city suburb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Studies have also identified higher levels of serum biomarkers as obesity risk factors: hypercholesterolemia , triglycerides , and high‐density lipoprotein cholesterol . Low fruit and vegetable intake (<3 times/week) , a preference for fatty foods , and consumption of particular foods (e.g., meat, rice, potatoes) were also risk factors for childhood obesity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have also identified higher levels of serum biomarkers as obesity risk factors: hypercholesterolemia , triglycerides , and high‐density lipoprotein cholesterol . Low fruit and vegetable intake (<3 times/week) , a preference for fatty foods , and consumption of particular foods (e.g., meat, rice, potatoes) were also risk factors for childhood obesity.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies found that having few or no siblings was a risk factor for childhood obesity (106,204). Two studies (44,156) found that smaller household size was a risk factor, whereas another study (51) found the opposite. One study (153) found that parents who lived separately before the birth of child (versus together) were more likely to have a child identified as obese.…”
Section: Maternal Agementioning
confidence: 99%
See 1 more Smart Citation
“…Eating habits are closely connected with body mass and children's way of life [4]. Disordered eating behavior and messy food influence on adolescents' body composition [9,23,37].…”
mentioning
confidence: 99%
“…Furthermore, epigenetic mechanisms (gene-environment interactions) during developmentally vulnerable periods of life increase further the risk for obesity. Familial, socioeconomic, and lifestyle parameters have Family Relations 65 (February 2016): 85-93 been also associated with obesity in children (Birbilis, Moschonis, Mougios, Manios, & The Healthy Growth Study Group, 2013;Bracale et al, 2015;Manios et al, 2013;Moschonis et al, 2014). A recent study by Hernandez and Pressler (2015) showed that family disruption and conflict, financial stress, exposure to maternal health risk behaviors, and total cumulative stress are associated with adolescent obesity.…”
mentioning
confidence: 99%